Characteristics of bullying in ninth grade adolescents. Abreus, Cienfuegos, 2021-2022 - Marioly Ruiz Hernandez; Honey Turiño Matamoros; Yanara Calzada Urquiola; Laura Magda López Angulo; Daniela de la Caridad Cedeño Díaz (Medisur, 2025)
Foundation: adolescents who suffer from bullying are a cause for concern for global public health. Therefore, analyses are required that identify the presence of this phenomenon on a medium and large scale in the corresponding settings. Objective: to characterize bullying in ninth grade adolescents. Methods: A descriptive cross-sectional study was conducted at the Adolfo Ortiz Fonte Mixed School in Abreus, from September 2021 to June 2022. The sample consisted of 19 adolescent students from said school, who claimed to have been victims of bullying in the preceding six months. A questionnaire (validated by experts) was designed and applied that evaluated the particularities of perceived bullying through variables such as expression of bullying, precipitating factors and frequency, among others. Results: Females were more affected by the phenomenon of bullying. Psychological bullying was the most frequent (100%), followed by physical bullying (21.1%). Place of residence and skin color were identified as the main causes, while school hallways, backyards  and bathrooms were listed as the most common places of aggression. The main perceived consequences were emotional (78.9%). Conclusion: The low perception of bullying within the studied universe, with psychological bullying being the most frequent form of expression, linked to the emotional consequences that arise from it.